Dansk musikvidenskabs integration af Adlers stilkoncept: En ny betingelse for tænkningen af musikalsk subjektivitet i det 20. århundrede - Pio, Frederik (Danish Yearbook of Musicology, 2002)
The article, “The integration of the Adler concept of style in Danish musicology. A new prerequisite for the understanding of musical subjectivity in the 20th century”, investigates how Guido Adler’s concept of ‘Style’ is installed in Danish musicology during the second and third decade of the 20th century. The Adlerian concept of ‘der Stil’ is considered as a symptom, not only of a change in the definition of method and object of historical musicology, but also as a symptom of a general transformation of the musicological institution as such. In other words, the formation of the musicological institution in Denmark during the second and third decade of the 20th century provides a new answer to the old question: what is the science of music? This innovation reflects – as indicated by the concept of style – a loyalty to the famous Adlerian concept of a general ‘Musikwissenschaft’. ‘Der Stil’ becomes a synthetic concept which as a theoretical emblem is superposed on this general conception of a science. The article asserts that the above mentioned ‘new answer’ – established within this horizon of style – must be considered a fundamental prerequisite to the way in which musical subjectivity is decided and fixed by means of the 20th century concept ‘Musikalität’ (musicality). In other words, the new musical knowledge of science becomes a grid through which modern musical man is now reconsidered.